Comparative study of magnetic properties and the anticancer effect of superparamagnetic and ferromagnetic iron oxide nanoparticles in the nanocomplex with doxorubicin - Orel, V. E.; Shevchenko, A. D.; Rykhalskyi, O. Yu.; Romanov, A. V.; Orel, I. V.; Lukin, S. N.; Burlaka, A. P.; Venger, E. F. (Reports of the National Academy of Sciences of Ukraine, 2015)
Mechano-magneto-chemically synthesized magnetic nanocomplex (MNC) of superparamagnetic iron oxide Fe3O4 nanoparticles (NP) and anticancer drug doxorubicin (DR) had significantly lower saturation magnetic moment and magnetic hysteresis loop area as compared to the MNC of ferromagnetic NP. However, the last was characterized by lower coercivity. MNC of superparamagnetic NP and DR had g-factors of 2.00, 2.30, and 4.00. MNC of ferromagnetic NP and DR had the g-factor of 2.50, and the integrated intensity of electron spin resonance signals was by 61% greater. Superparamagnetic iron oxide Fe3O4 NP in MNC with DR initiated a greater antitumor effect during magnetic nanotherapy of animals with carcinosarcoma Walker-256 as compared to the MNC composed of ferromagnetic NP and DR. In the future, superparamagnetic iron oxide Fe3O4 NP as a part of the nanocomplex with DR can be used in theranostics – a methodology that combines magnetic resonance diagnostics and magnetic nanotherapy using MNC both as therapeutic and diagnostic agents.